Towards open access social orders in Eastern Europe. Issue 1 (2nd January 2021) - Toshkov, Dimiter; Dimitrova, Antoaneta; Börzel, Tanja
ABSTRACT: This article introduces a special issue that investigates the interplay between domestic socio-political orders and changing external influences – of the EU, Russia, Turkey and other external actors in the region. In this introduction, we lay the conceptual framework and propose theoretical mechanisms linking state capacity and the actions of external actors to the likelihood of transformations from limited to open access orders. Previewing the findings, we note a fundamental asymmetry: while external actors have many levers to undermine the establishment of an open access order, they are more limited in how they can support reforms towards liberal democracy and free-market economy.